Clinical trial transparency in gastrointestinal endoscopy research - Garg, Shashank; Rizvi, Anam; Wee, Diana; Rizvi, Youshaw; Rizvi, Fatima; Rizvi, Anza; Thomas, Sheila Louise; Inamdar, Sumant; Trindade, Arvind J. (Endoscopy, 2022)
Background Under-reporting of clinical trial results can lead to negative consequences that include inhibiting propagation of knowledge, limiting the understanding of how devices work, affecting conclusions of meta-analyses, and failing to acknowledge patient participation. Therefore clinical trial transparency, through publication of trial results on ClinicalTrials.gov or in manuscript form, is important. We aimed to examine clinical trial transparency in endoscopic clinical trials.Methods The ClinicalTrials.gov database was searched for endoscopy trials up to October 2019. Adherence to the reporting of results to the database or in publication form was recorded for each trial.Results The final analysis included 923 trials, of which 801 were completed and 122 were either terminated or suspended. Results were available either on ClinicalTrials.gov or in publication for 751/923 trials (81.4 %). Other fields have reported a publication rate of 40 %–63 %. Results were available on ClinicalTrials.gov for 168 trials (18.2 %) and in the form of a publication for 720 trails (78.0 %).Conclusions Compared with other fields in medicine, endoscopy clinical trials have a high rate of clinical trial transparency. However, there is room for improvements as close to one-fifth of trials fail to report results and 81.8 % do not report results to ClinicalTrials.gov.